IMPLEMENTASI KURIKULUM 2013 DAN PENDIDIKAN KARAKTER - Oktarina, Ririn (Graduate Program Magister Manajemen Pendidikan, 2018)
In this article, I described the implementation of curriculum 2013 and character education in SD Negeri 8 Rambutan, Banyuasin. Since validity of curriculum 2013, this school did the curriculum for first and fourth class, while other class used KTSP. At first appearance of curriculum 2013, this school asked some teachers to follow exercise of curriculum 2013. Then, the teachers were able to implement curriculum 2013 in teaching class. In educational character it implant social values such as religius, national, stand alone, mutual cooperation and integrity. In implementation of curriculum 2013, it also organized school literature program that purposed to form character of children in order to be dilligent and liked reading.